PENGARUH ASPEK PERMODALAN, KUALITAS PIUTANG PEMBIAYAAN, PROFITABILITAS DAN LIKUIDITAS PERUSAHAAN PEMBIAYAAN TERHADAP PERTUMBUHAN LABA - INTAN SARI, YUNITA (Jurnal Akuntansi AKUNESA, 2017)
The purpose of this research is to determine the effect of capital aspect, quality of receivables financing, profitability, and liquidity on profit growth in financing companies. Capital aspect is measured by paid up capital-equity ratio, quality of receivables financing is measured by nonperforming financing, profitability is measured by return on asset, and likuidity is measured by current ratio. This research used 23 financing companies listed on Indonesia financial services authority during period of 2011 until 2015. The result showed that capital aspect, profitability, and liquidity have no effect on profit growth, but quality of receivables financing has negative effect on profit growth. Keyword:   paid up capital-equity ratio, nonperforming financing, return on asset, current ratio, profit growth